Dose-Dependent Blood-Feeding Activity and Ovarian Alterations to PM2.5 in Aedes aegypti - Thipruethai Phanitchat; Sumate Ampawong; Artit Yawootti; Thammanitchpol Denpetkul; Napid Wadmanee; Mongkhon Sompornrattanaphan; Chaisith Sivakorn (Insects, 2021)
High levels of fine particulate matter (PM2.5) air pollution are a concern for human health. Several studies have examined the effects of air pollution on human and animal health. However, there is a lack of knowledge about its effects on arbovirus vectors. Thus, we investigated whether PM2.5 concentration alters the blood-feeding activity of Ae. aegypti mosquitoes. We investigated the effect on the females’ propensity to blood feed at eight concentrations of PM2.5 ranging from 100 to 1000 μg/m3. Correlation analysis showed blood-feeding activity had a significant strong negative correlation with concentration of PM2.5 (rp = −0.85; p ≤ 0.00001). Exploratory linear and non-linear models showed an exponential decay relationship was the best fitting model (corrected Akaike’s information criterion, 193.0; Akaike’s weight, 0.766; adjusted R2, 0.780). Ultrastructural study demonstrated PM2.5 did not obstruct the respiratory system, but some fine particles were present on the antenna and abdominal body parts. Ovaries showed a dose–response relationship between PM2.5 level and vacuolated degeneration. In conclusion, the blood-feeding behavior of Ae. aegypti females may have an exponential decay relationship with PM2.5 level, and their ovaries may demonstrate dose-dependent degeneration. These findings may be important in understanding the vector’s biology and disease transmission in settings with high PM2.5 levels. These results are important to understand blood-feeding and feeding pattern of mosquitoes during PM2.5 pollution, which is important for disease transmission and vector control.